Behind the scenes of Science: argumentation, history, and philosophy in Physics teaching - França, Érika Cristina Meneses de; Leal, Aline Dortas (Linha D'Água, 2023)
Research in the field of science education has shown the significance of historical-philosophical approaches and argumentation for a reflective education. This article aims to understand the importance of the history and philosophy of science in relation to the teaching of argumentation in Physics, with a focus on Newton's laws. To this end, a literature review on the subject was conducted, followed by the development and application of activities with high school students in a state public school in Aracaju, (Sergipe, Brazil). The results indicate the development of a more contextualized understanding of science, the inclusion of scientific procedures such as the construction of explanations and the use of justifications, the increased sophistication of the arguments as the topics discussed involved social and ethical aspects, and the mobilization of knowledge acquired inside and outside Physics classes.